Strategic Management of Angklung Pedagogy in Islamic Education: Optimizing Student Holistic Potential - A Wathon (Lembaga Yasin AlSys, 2026)
Although the recognition of cultural arts within holistic education is increasing, the integration of traditional music pedagogy, such as Angklung music, into the framework of Islamic education management has not yet been systematically explored. This study aimed to analyze the development, implementation, and evaluation of a strategic management model for Angklung music learning in Islamic educational institutions by highlighting its effectiveness in optimizing students’ potential. Using a qualitative research design, the study examined pedagogical approaches, leadership roles, and institutional support mechanisms required for the successful integration of Angklung music learning into Islamic education management. The findings indicate that a well-structured Angklung program supported by Islamic management principles significantly enhances students’ cognitive, affective, and psychomotor skills, while simultaneously fostering cultural identity and spiritual growth aligned with Islamic values. The study concludes that such an integrated approach is essential for enriching educational practice and nurturing well-rounded individuals, as well as contributing to the development of theoretical frameworks for leadership and Islamic education management. The implications of this research include practical recommendations for curriculum developers and administrators of Islamic educational institutions to integrate cultural arts more effectively, and it opens avenues for further exploration of other forms of traditional arts within the context of Islamic education.